Study On Function Facilities Utilization Of Tiku Fishing Port At Agam District Of West Sumatera Province - Rissa Julia Putri; Alit Hindri Yani; Isnaniah Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThe purpose of this research is to determine the utilization of functional facilities of Tiku fishing port. This research was conducted in April 2018. The method used in this research is survey method by conducting observation and collecting data directly. Data analysis using facility requirement analysis and facility utilization level analysis. Surveys show that existing functional facilities are fish market halls, clean water tanks, fuel tanks, ice factories, cold storage and fishing packages. Of the 6 existing facilities only 2 facilities are analyzed level of utilization of facilities. Based on the results of the analysis can be seen that the level of ice factory needs is 79.5% pertained to use and 90% fuel tank classified as being utilized. Keyword: Fishing Port, Functional Facilities, Utilization Level